2011
DOI: 10.1021/bc200572w
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Library of Lipidoids for In Vitro DNA Delivery

Abstract: A combinatorial library of lipidoids was constructed and studied for in vitro gene delivery. The library of lipidoids was synthesized by reacting commercially available amines with lipophilic acrylates, acrylamides, or epoxides. Lipidoids derived from amine 86 (N,N-Bis(2-hydroxyethyl)ethylene diamine) and amine 87 (N-(3-aminopropyl)diethaneamine) showed high efficiency in DNA delivery, some with a higher transfection efficiency than Lipofectamine 2000, a commonly used commercial gold standard for in vitro gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 18 publications
0
65
0
Order By: Relevance
“…Lipidoid 14N-87 109c was able to encapsulate up to 70% DNA, while 14O-87 109l and 16C-87 109z were able to encapsulate 82% and respectively 55%, as revealed by a picogreen assay. 186 108g, 109g, 110b and 111b. Moreover, the same unsaturated lipidoids were found at least 50% more efficient than LFM2000 for mRNA delivery into HeLa cells, but were found less potent than the commercial transfection system in delivering DNA in the same cell line.…”
Section: Oligomeric Amphiphilesmentioning
confidence: 99%
“…Lipidoid 14N-87 109c was able to encapsulate up to 70% DNA, while 14O-87 109l and 16C-87 109z were able to encapsulate 82% and respectively 55%, as revealed by a picogreen assay. 186 108g, 109g, 110b and 111b. Moreover, the same unsaturated lipidoids were found at least 50% more efficient than LFM2000 for mRNA delivery into HeLa cells, but were found less potent than the commercial transfection system in delivering DNA in the same cell line.…”
Section: Oligomeric Amphiphilesmentioning
confidence: 99%
“…Recently, we developed lipid-like nanoparticles that can be synthesized in a combinatorial manner as highly effective protein and gene delivery vehicles (9)(10)(11)(12)(13). We found that electrostatic selfassembly between lipid and protein is essential to form a stable nanocomplex for protein delivery (11).…”
mentioning
confidence: 99%
“…The cationic poly(-amino ester) library of over 5,000 different constituents was then screened for use in non-viral gene therapy using plasmid DNA and siRNA delivery. Selection of "hits" from the poly(-amino ester) library allowed for further modification of the backbone structure to include lipid functionality and formulation of lipidoid-based nano-vesicles for siRNA encapsulation (10,(19)(20)(21).…”
Section: Combinatorial-designed Nanoparticlesmentioning
confidence: 99%